Extent does the primary school mathematics teachers in Makkah Al-Mukarramah aware of the manifestations of difficulties in learning arithmetic (dyscalculia) among female students - Al-Afifi, Sawsan Ahmed (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify to what extent does the primary school mathematics teachers in Makkah Al-Mukarramah aware of the manifestations of difficulties in learning arithmetic (dyscalculia) among female students. To achieve the aim of the study, the descriptive survey approach was followed and the study tool, which was the questionnaire, was built. The study sample consisted of (170) female teachers who teach mathematics in Governmental schools in Makkah Al-Mukarramah.The study concluded that the degree of awareness of mathematics teachers at the primary stage in Makkah Al-Mukarramah about the manifestations of difficulties in learning arithmetic was (moderate).The results also showed that there were no statistically significant differences at the function level (0.05) in the degree of female teachers’ awareness of the manifestations of difficulties in learning arithmetic, according to the variables of education and years of experience.Based on the results, the researcher recommended the need to hold training courses for mathematics teachers to identify the difficulties of learning arithmetic among students, including determining the appropriate methods when teaching them, and the diversity in the use of strategies, methods, and teaching aids when teaching mathematics, in a way that addresses the learner cognitively, skillfully, and emotionally.
Keywords: dyscalculia; difficulties in learning arithmetic; primary stage